Effects of social media tourism information quality on destination travel intention: Mediation effect of self-congruity and trust - Wang, Huimin; Yan, Jinzhe (Frontiers in Psychology, 2022)
The asymmetry of tourism information makes social media an important information source. Previous research has been conducted on the influence of tourist-generated content on tourism consumption behavior, but few studies have concentrated on the mechanism of tourism information quality on consumers’ travel intention in the social media environment. Adopting the Elaboration Likelihood Model, this paper aims to investigate how the information quality of social media affects consumers’ travel intention rationally and emotionally and the moderation effect of tourists’ prior knowledge. The empirical results indicate that the quality of social media information positively affects travel intention and self-congruity and trust mediates the relationship between the quality of social media information and travel intention. Moreover, this study identified that tourists’ prior knowledge negatively modifies the relationship between information quality and self-congruity in line with the proposed hypotheses. The research explores the influence mechanism of tourist-generated content quality on consumers’ travel intention, which benefits destination management and content marketing.